Diffusion-weighted MR imaging of non-complicated hepatic cysts: Value of 3T computed diffusion-weighted imaging. (2016) - Nakamura, Yuko; Higaki, Toru; Akiyama, Yuji; Fukumoto, Wataru; Kajiwara, Kenji; Kaichi, Yoko; Honda, Yukiko; Komoto, Daisuke; Tatsugami, Fuminari; Iida, Makoto; Ohmoto, Toshifumi; Date, Shuji; et al.
Abstract: Purpose: To investigate the utility of computed 3T diffusion-weighted imaging (c-DWI) for the diagnosis of non-complicated hepatic cysts with a focus on the T2 shine-through effect. Materials and methods: In 50 patients with non-complicated hepatic cysts we acquired one set of DWIs (b-value 0 and 1000 s/mm 2 ) at 1.5T, and two sets at 3T (b-value 0 and 1000 s/mm 2, TE 70 ms; b-value 0 and 600 s/mm 2, TE 60 ms). We defined the original DWIs acquired with b = 1000 s/mm 2 at 1.5T and 3T as "o-1.5T-1000" and "o-3T-1000". c-DWIs were calculated with 3T DWI at b-values of 0 and 600 s/mm 2 . c-DWI with b = 1000 and 1500 s/mm 2 were defined as "c-1000" and "c-1500". Radiologists evaluated the signal intensity (SI) of the cysts using a 3-point score where 1 = not visible, 2 = discernible, and 3 = clearly visible. They calculated the contrast ratio (CR) between the cysts and the surrounding liver parenchyma on each DWIs and recorded the apparent diffusion coefficient (ADC) with a b-value = 0 and 1000 s/mm 2 on 1.5T- and 3T DWIs. Results: Compared with o-1.5T-1000 DWI, the visual scores of all but the c-1500 DWIs were higher (p = 0.07 for c-1500- and p < 0.01 for the other DWIs). The CR at b = 1000 s/mm 2 was higher on o-3T-1000- than on o-1.5T-1000- (p < 0.01) but not higher than on c-1500 DWIs (p = 0.96). The CR at b = 0 s/mm 2 on 3T images with TE 70 ms was higher than on 1.5T images (p < 0.01). The ADC value was higher for 3T- than 1.5T images (p < 0.01). Conclusions: Non-complicated hepatic cysts showed higher SI on o-3T-1000- than o-1.5T-1000 DWIs due to the T2-shine through effect. This high SI was suppressed on c-1500 DWIs.